Compliance to donning and doffing of personal protective equipment among dental healthcare practitioners during the coronavirus pandemic: a quality improvement plan, do, study and act (PDSA) Initiative. Issue 3 (28th September 2022) - Qabool, Hafsa; Ali, Faiza; Sukhia, Rashna Hoshang; Badruddin, Naila
Abstract : Introduction: With the emergence of SARS-Cov-2, the Centers for Disease Control and Prevention (CDC) defined mandatory guidelines for donning and doffing personal protective equipment (PPE) among dental healthcare professionals. The study's objective was to improve the compliance of the donning and doffing protocols for PPE among dental practitioners by the Plan, Do, Study, and Act (PDSA) cycle. Materials and methods: A quasi-experimental study was conducted on a sample of dental healthcare professionals using the non-probability purposive technique. In the first planning stage, compliance with CDC-approved donning and doffing was assessed on the clinical premises. In the second stage, an educational session was arranged with all the healthcare professionals to explain stepwise guidelines of donning and doffing to improve the quality of donning and doffing compliance. In the third stage, improvement in the quality outcome was then assessed after the session. Data were normally distributed. Qualitative variables for all the steps of donning and doffing are reported as frequency and percentages. Pareto charts were made to assess the non-compliance rate for donning and doffing protocols among dental healthcare professionals. Results: There was an improvement of 44.55% in the hand hygiene practices before wearing the PPE after the second step of the PDSA cycle. A percentage improvement of 7.4% was recorded for removing jewellery, wearing the gown and wearing a surgical cap. No improvement was seen in securing the mask/ respirator ties, washing hands after wearing the respirator, placing the goggles or face shield practices. Conclusions: PDSA cycle improved the overall compliance to PPE donning and doffing practices. Most of the protocols were followed by the dental healthcare professionals; however, some of them remained the same or worsened due to ease in SARS-CoV 2 restrictions.